Reconceptualizing Ecological Da'wah: Integrating Theology, Ethics, and Socio-Environmental Practice - Muchlis; Mahmudi; Syarif , Zainuddin; Hosaini (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
This study critically addresses the marginalized position of environmental concerns in mainstream Islamic da'wah discourse by examining ecological da'wah as a systematically underdeveloped yet theologically grounded dimension of Islamic da'wah. Although environmental ethics is well established in Islamic theology, its translation into a da'wah framework remains fragmented and largely normative. In response to this gap, this study aims to reconceptualize ecological da'wah not merely as moral exhortation but as an integrative da'wah paradigm that connects theology, ethics, and socio-ecological practices. Using a qualitative sociological approach, this study draws on field observations, interviews, and empirical data from ongoing da'wah practices in the community, which are then analyzed using thematic content analysis techniques. Rather than rehashing established ethical concepts, this analysis critically reinterprets the key theological principles of khalifah (stewardship), amanah (trust), and mizan (cosmic balance) as operational categories for da'wah engagement with the ecological crisis. The findings of this study indicate that ecological da'wah has strategic potential to reshape religious communication by embedding environmental responsibility within theocentric moral reasoning and lived religious practices. However, the study also identifies structural and discursive constraints, including the dominance of anthropocentric models of da'wah and the absence of institutionalized ecological narratives within da'wah agendas. This study contributes to da'wah scholarship by offering a conceptual framework for ecological da'wah as a transformative and context-responsive model of Islamic da'wah. By repositioning environmental preservation as an integral component of religious responsibility, this study advances a theoretically grounded approach that enhances the relevance of Islamic da'wah in addressing contemporary global ecological challenges.